Moral and Character Education: An Analysis - Bujang Bujang; Azizah Khaira Ummah; Bahera Bahera (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2023)
This article aims to describe moral and character education. The research method used is library research. Character education is an effort to cultivate and shape character that emphasizes the importance of the three components of good character (components of good character), namely moral knowing or knowledge of morals, moral feeling or feelings about morals and moral action or moral actions. Then the areas of character education include: moral reasoning or cognitive development, social and emotional learning, moral virtue education, life skills education, health education, violence prevention, conflict resolution, and ethical or moral philosophy. Moral education is a conscious and unconscious effort made by an educator to form good habits in a student, so that a human being is formed who is obedient to god. Character education or moral education is a necessity to reduce the multidimensional crisis that has hit Indonesia. To be effective, character education must involve three bases. First, class basis, where the relationship between teachers and students occurs. Second, the basis of school culture, namely building a school culture that is able to shape the character of students, and third, the basis of community, namely family, society and the State must also build character which is reflected in daily life patterns.